If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 4 = 4x + 39 Reorder the terms: 4 + 11x = 4x + 39 Reorder the terms: 4 + 11x = 39 + 4x Solving 4 + 11x = 39 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 4 + 11x + -4x = 39 + 4x + -4x Combine like terms: 11x + -4x = 7x 4 + 7x = 39 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + 7x = 39 + 0 4 + 7x = 39 Add '-4' to each side of the equation. 4 + -4 + 7x = 39 + -4 Combine like terms: 4 + -4 = 0 0 + 7x = 39 + -4 7x = 39 + -4 Combine like terms: 39 + -4 = 35 7x = 35 Divide each side by '7'. x = 5 Simplifying x = 5
| 9/7x-6=17 | | 3y=-2x-12 | | 3/4x-2=-1 | | (1.2)(Y-2)=3300 | | 5-6n-6=-13 | | (1.2)x(Y-2)=3300 | | y=.75x=1/2 | | 3n+2=-11 | | 3(11r-13)=-7r+57 | | m^3+6m^2=27m | | n(n-3)=88 | | 5x-3=10x+6 | | n+6n=15+2n | | 4p^2-4p-7=0 | | x/3=3129 | | 2(x+10)=90 | | 5x+50y=100 | | x/2=92 | | 7x-9w=solve | | 18x=-3x | | 2xy+5x-12y-30= | | (7y+6)+(4y)+(116)=180 | | 4z/9-6=7 | | 7x+6y=92 | | -2=1/5x-9 | | 4x-3-2x+4=2x-1 | | 4(2xy-5)=22 | | n-7+2=-4(2n+8)+4(5+2n) | | 3x+8-6(x+1)=5x+7 | | 4x-90=-10x+36 | | x/5=200 | | 11x-40=6x+5 |